Inalienability in North Saami - Lene Antonsen; Laura Janda (Sámi dieđalaš áigečála)
On the basis of corpus data (9.5M words 1997–2010) we claim that North Saami is developing a grammatical distinction between alienable and inalienable possession. In previous work we documented a language change in North Saami in which the possessive suffix as in girjji-id-easkka [book-acc.pl-3pl] ‘their books’ is being replaced by an analytic construction with the reflexive genitive ieža-form, as in iežaska girjjiid ‘their books’. According to typologists, alienable/inalienable distinctions arise primarily in small languages where a language change takes place, and inalienability is marked by the synthetic construction. North Saami possessive constructions comport with these features, and the possessive suffix tends to mark inalienable possession, as opposed to the more neutral and widespread ieža-form. Statistical analysis shows that word frequency cannot account for the distribution of the possessive suffix vs. ieža-form, justifying focus on semantics. North Saami shows high frequency of the possessive suffix for kinship and body part nouns associated with inalienability cross-linguistically, but there is a strong presence of the possessive suffix with words for “products”: concrete and abstract human artefacts, where the creation is inalienably possessed by its creator. Another important group marked with the possessive suffix associated with inalienable possession are words connected with identity and livelihood. Even though overall the reflexive genitive ieža-form has been taking the place of the possessive suffix the possessive suffix, continues to be productive in use with words signaling products, identity, and livelihood.